PENGARUH MEDIA SOSIAL YOUTUBE TERHADAP PRESTASI BELAJAR MAHASISWA PENDIDIKAN EKONOMI STAMBUK 2018 UNIMED (Magister Manajemen Universitas Wisnuwardhana, 2023)
Abstract. This studi aims to determine the effect of Youtube Learning Media on student achievment in economics Education at the State University f Medan. The type of research is quantitative research using IBM SPSS version 22. Data collection techniques are through questionnaries, observation and documentation. The result of the study show that there is a positive and significant effect of Youtube Learning Media on learning achievment where t acount was 7.638 which was greater than the t table of 1,990.